Aplikasi Kasir Online Berbasis QR-Code pada Toko Emas Karunia Cepu - Muksan Junaidi; Khalif Rifky Noor Nugroho; Eka Satria Wibawa (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Karunia gold shop, as one of the gold trading retail players, has several branches in Cepu City and its surroundings. In order to improve operational sales efficiency, this shop will adopt the latest technology by implementing a sales information system. The purpose of this study is to develop an online cashier system based on QR Code at the Karunia gold shop for purchase/sale and payment transactions. Jewelry transaction data from 2018 was IDR 150,594,000, in 2019 it was IDR 109,309,000, and 2020 it was IDR 120,683,000. The structural model system development method uses web-based PHP programming and a MySql database. The results of the black box testing of the new system obtained a functional value of 72.3%. The final result is an Online Cashier System with QR Code which has the potential to increase transaction speed, facilitate gold stock management, and provide a different experience to customers in making effective, efficient and better transactions.